Do We Need Titanium Dioxide (TiO2) Nanoparticles in Face Masks? - Stijn Everaert; Lode Godderis; Jean-Marie Raquez; Greet Schoeters; Pieter Spanoghe; Jonas Moens; Luc Hens; Olivier Michel; Dirk Adang; Norbert Fraeyman (Toxics)
The use of face masks has proven to be an effective preventive measure during the COVID-19 pandemic. However, concerns have emerged regarding the safety of metal (nano)particles incorporated into face masks for antimicrobial purposes. Specifically, this review examines the risks associated with TiO2 nanoparticles (NPs), which are classified as a possible human carcinogen. The inhalation of TiO2 NPs can cause multiple adverse effects, including oxidative stress, pulmonary inflammation, histopathological changes, and (secondary) genotoxicity. Different aspects are discussed, such as the composition and filtration efficiency of face masks, the antimicrobial mode of action and effectiveness of various metals, and the hazards of TiO2 NPs to human health, including exposure limits. A conservative risk assessment was conducted using different worst-case scenarios of potential (sub)chronic TiO2 exposure, derived from published leaching experiments. Most face masks are considered safe, especially for occasional or single use. However, the nanosafety of a minority of face masks on the European market may be inadequate for prolonged and intensive use. Important uncertainties remain, including the risks of combined exposure to TiO2 NPs and silver biocides, and the lack of direct exposure measurements. Considering the potential safety issues and the limited added protective value of TiO2 NPs, it is recommended to ban all applications of TiO2 in face masks based on the precautionary principle.